Instructional Technology and Higher Education Rewards, Rights, and Responsibilities - Albright, Michael J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
This keynote address seeks to establish a definition for "instructional technology" that does not emphasize computer hardware and software but instead focuses on human skills, resource management, problem solving, and educational settings. Also discussed are ways in which technology like electronic mail and the world wide web has penetrated institutions of higher learning and has caused shifts in learning and instructional paradigms. Barriers to faculty use of instructional technology range from a lack of administrative commitment to poorly equipped classrooms and disproportionate access. So many barriers exist, in fact, that much of what faculty has accomplished with technology has happened in spite of, rather than because of, the campus environment. This paper concludes that faculty have the right to: (1) a reward system that places a high value on teaching and innovative teaching methods in addition to research activities; (2) an institutional climate that encourages the use of technology; (3) an institutional commitment to technology in university planning documents and budget appropriations; (4) an administration that sets the pace via its own use of technology; (5) a campuswide instructional technology support infrastructure; (6) easy access to technology-based display systems in the classroom, to course development resources, and to consultation and production support services; and (7) training programs related to classroom technology applications. This kind of milieu is crucial because students and employers expect universities to produce a workforce versed in the technologies of our information-rich society. (Contains 22 references and 30 a list of additional resources.) (BEW)
ERIC Note: Keynote address presented at the Southern Regional Faculty and Instructional Development Consortium (Baton Rouge, LA, February 5, 1996).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Computers; Administrator Responsibility; Classroom Techniques; College Faculty; Educational Equipment; Educational Technology; Faculty Development; Higher Education; Instructional Innovation; Organizational Change; Problem Solving; Teacher Education; Technological Advancement; Barriers to Innovation -- Instructional Support Services; Opinion Papers; Speeches/Meeting Papers